NF-κB inhibits TNF-induced accumulation of ROS that mediate prolonged MAPK activation and necrotic cell death - Sakon, Sachiko (Oxford University Press, 2003)
NF-κB downregulates tumor necrosis factor (TNF)-induced c-Jun N-terminal kinase (JNK) activation that promotes cell death, but the mechanism is not yet fully understood. By using murine embryonic fibroblasts (MEFs) that are deficient in TNF receptor-associated factor (TRAF) 2 and TRAF5 (DKO) or p65 NF-κB subunit (p65KO), we demonstrate here that TNF stimulation leads to accumulation of reactive oxygen species (ROS), which is essential for prolonged mitogen-activated protein kinase (MAPK) activation and cell death. Interestingly, dying cells show necrotic as well as apoptotic morphological changes as assessed by electron microscopy and flow cytometry, and necrotic, but not apoptotic, cell death is substantially inhibited by antioxidant. Importantly, TNF does not induce ROS accumulation or prolonged MAPK activation in wild-type MEFs, indicating that TRAF-mediated NF-κB activation normally suppresses the TNF-induced ROS accumulation that subsequently induces prolonged MAPK activation and necrotic cell death